NILAI-NILAI PENDIDIKAN ISLAM: (Tela’ah Novel Kasidah-Kasidah Cinta) - Nurul Indana; Noor Fatikah; Nady Nady (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
Along with development of globalization, literary works also makes an important contribution to education. One of the novels that included Islamic values ??especially in moral messages is the novel